Foreword - Epure, Manuela (Journal of Economic Development, Environment and People, 2016)
More and more, the today’s economic debates gravitate around the Fourth Industrial Revolution and the global transformation characterized by the digital, physical and biological technologies that interfere and change the world around us and our perception of the humankind progress.